The People, the Priests and the Protestants: Catholic Responses to Evangelical Missionaries in the Early Nineteenth-Century Scottish Highlands. Issue 2 (27th May 2016) - Ritchie, Elizabeth
Abstract : From the 1810s into the 1830s evangelical missionaries worked among Scottish Highland Catholic communities with the co-operation and assistance of the people and their priests. The historiography of protestant-Catholic relations is dominated by conflict and that of nineteenth-century Scotland focuses on tension in the industrializing Lowlands. However, the key religious issue for Highland Catholics was the response to expansionist protestantism. The Edinburgh Society for the Support of Gaelic Schools (ESSGS) best epitomizes this movement. Letters from priests and the society's annual reports reveal how long-established rural Catholic communities reacted to missionary activity and how, building on the tense compromises of the eighteenth century, for a few decades evangelicals and Catholics co-operated effectively. The ESSGS learned to involve local priests, provide sympathetic teachers and modify the curriculum. Catholics drew on their experience as a disempowered minority by resisting passively rather than actively and by using the society's schools on their own terms. Many Catholic parents and clergy developed a modus vivendi with evangelicals through their common interest in educating children. The evidence of northwest Scotland demonstrates how a minority faith group and missionaries negotiated a satisfactory coexistence in a period of energetic evangelical activity across the British world.